P-tau235: a novel biomarker for staging preclinical Alzheimer's disease - Lantero-Rodriguez Juan; Snellman Anniina; Benedet Andrea L; Milà-Alomà Marta; Camporesi Elena; Montoliu-Gaya Laia; Ashton Nicholas J; Vrillon Agathe; Karikari Thomas K; Gispert Juan Domingo; Salvadó Gemma; Shekari Mahnaz; et al. (WILEY, 2025)
Alzheimer's disease (AD) is characterised by a long preclinical phase. Although phosphorylated tau (p-tau) species such as p-tau217 and p-tau231 provide accurate detection of early pathological changes, other biomarkers capable of staging disease progression during preclinical AD are still needed. Combining exploratory and targeted mass spectrometry methods in neuropathologically confirmed brain tissue, we observed that p-tau235 is a prominent feature of AD pathology. In addition, p-tau235 seemed to be preceded by p-tau231, in what appeared to be a sequential phosphorylation event. To exploit its biomarker potential in cerebrospinal fluid (CSF), we developed and validated a new p-tau235 Simoa assay. Using three clinical cohorts, we demonstrated that (i) CSF p-235 increases early in AD continuum, and (ii) changes in CSF p-tau235 and p-tau231 levels during preclinical AD are consistent with the sequential phosphorylation evidence in AD brain. In conclusion, CSF p-tau235 appears to be not only a highly specific biomarker of AD but also a promising staging biomarker for the preclinical phase. Thus, it could prove useful tracking disease progression and help enriching clinical trial recruitment.